Keefektifan Media Audio Visual dengan Bantuan GC 5 Tiga Dimensi Materi Bangun Geometri Kelas V SD YPNU Medan - Nuri Ramadhan; Thessa Herdyana (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research is a development study that aims to create a product in the form of a learning aid, namely audio-visual media through the GeoGebra Classic application, which is used for 3-dimensional geometric shapes lessons in grade V of YPNU Elementary School Medan. This research was conducted because teachers still do not utilize technology optimally in teaching, especially in mathematics subjects related to spatial shapes. The lack of engaging and interactive teaching methods for complex topics like 3D geometric shapes often leads to reduced student interest and understanding. To improve the mathematics learning process on the topic of spatial shapes, audio-visual media was created with the help of the GeoGebra Classic 5 application. The goal is to provide variations in mathematics learning media and increase student interest in the lesson. The development of this media allows students to visualize 3D geometric shapes more clearly and interactively. The instrument used to collect data was a questionnaire that included questions to assess the effectiveness of the media from the perspective of educators and students. The results of the evaluation revealed that learning using this media received 93% responses from teachers and 87% from students, which indicates that the media is very effective. The positive feedback from both groups suggests that this audio-visual tool can enhance students' understanding of spatial geometry concepts and improve the overall learning experience. This study offers an innovative approach to teaching mathematics and highlights the importance of integrating technology into the classroom to foster better engagement and learning outcomes.